2021
DOI: 10.1128/spectrum.01064-21
|View full text |Cite
|
Sign up to set email alerts
|

The Cultivation Method Affects the Transcriptomic Response of Aspergillus niger to Growth on Sugar Beet Pulp

Abstract: Understanding the interaction between filamentous fungi and their natural and biotechnological environments has been of great interest for the scientific community. Submerged cultures are preferred over solid cultures at a laboratory scale to study the natural response of fungi to different stimuli found in nature (e.g., carbon/nitrogen sources, pH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
(69 reference statements)
2
8
0
Order By: Relevance
“…The response to the presence of cellulose is most likely triggered when the pectin and hemicellulose content is depleting. The slow utilization of cellulose by A. niger was already described ( Garrigues et al., 2021 ; Kun et al., 2021 ), and is further supported by our growth profile results, showing growth only after long incubation times.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The response to the presence of cellulose is most likely triggered when the pectin and hemicellulose content is depleting. The slow utilization of cellulose by A. niger was already described ( Garrigues et al., 2021 ; Kun et al., 2021 ), and is further supported by our growth profile results, showing growth only after long incubation times.…”
Section: Discussionsupporting
confidence: 91%
“…However, the contribution of the major TFs to the overall degradation of sugar beet pulp by A. niger has not been reported in detail. Transcriptome data of the A. niger reference (CBS 138852) strain showed the preferential use of sugar beet pulp components of this fungus, which correlates with previously reported observations ( Garrigues et al., 2021 ). Our data confirmed that after 2 h, sucrose was the primary carbohydrate of sugar beet pulp utilized by A. niger .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In fact, previous studies revealed that a variety of culture conditions, e.g., solid vs. liquid, shaken vs. still, and high-density vs. low-density, have an extensive influence on microbial physiology [ 62 , 63 , 64 , 65 ]. In Aspergillus niger , the fungal transcriptomic response to sugar beet pulp was significantly different between solid culture and submerged culture, the latter inducing wider transcriptome variability [ 66 ]. Additionally, the fungal proteome and secretome complexity were affected by the cultivation modes in Aspergillus and Trichoderma species [ 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%